Banished the new social control in urban America - Beckett, Katherine, 1964-; Herbert, Steven Kelly, 1959- (Oxford : Oxford University Press, 2010)
With urban poverty rising, the homeless and other 'disorderly' people continue to occupy public space in many American cities. Drawing upon an extensive body of data, the authors chart the rise of banishment in Seattle, a city on the leading edge of this trend, to establish how it works and explore its ramifications.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Marginality, Social -- Washington (State) -- Seattle; Seattle (Wash.) -- Social policy